Nicotinic Acetylcholine Receptor Subtype Alpha-9 Mediates Triple-Negative Breast Cancers Based on a Spontaneous Pulmonary Metastasis Mouse Model - Huang, Li-Chi; Lin, Ching-Ling; Qiu, Jia-Zheng; Lin, Chun-Yu; Hsu, Kai-Wen; Tam, Ka-Wai; Lee, Jung-Yu; Yang, Jinn-Moon; Lee, Chia-Hwa (Frontiers in Cellular Neuroscience, 2017)
Triple-negative breast cancer (TNBC) subtype is associated with poor prognosis and a high risk of recurrence-related death in women. Despite the aggressiveness of TNBCs, targeted TNBC therapy is not yet available in the clinic. To overcome this challenge, we generated highly metastatic TNBC cells (LM) derived from metastasized lung cells via a serial spontaneous pulmonary metastasis animal model to identify targetable molecules for attenuating the progression of TNBC metastasis. Gene analysis of primary tumor (P), first-round (1LM) and second-round (2LM) metastasized lung cells revealed that mesenchymal-related genes were significantly expressed in LM cells, especially in 2LM cells. Interestingly, 9-nAChR gene expression was also dramatically induced in LM cells, confirming our previous finding that 9-nAChR plays important roles in receptor-mediated carcinogenic signals in human breast cancer development. Using 9-nAChR as a biomarker, we transfected 2LM cells with CRISPR/Cas9 lentivirus targeting the 9-nAChR genomic region (2LM-9-nAChR-null), showing that mesenchymal markers and the migration and invasion abilities of 2LM cells were significantly attenuated in 2LM-9-nAChR-null cells both in vitro and in vivo. In addition, the high efficiency of editing the 9-nAChR gene using a CRISPR/Cas9 lentivirus was demonstrated by gene sequencing, genomic indel frequency and protein expression analyses. Collectively, these results confirmed those of our previous study that advanced-stage breast tumors are associated with substantially higher levels of α9-nAChR gene expression, indicating that 9-nAChR expression is essential for mediating TNBC metastasis during cancer development and may potentially act as a biomarker for targeted therapy in clinical investigations.